Cell membrane damage by iron nanoparticles: an invitro study - Gelare Hajsalimi; Mojtaba Falahati (Islamic Azad University, 2016)
Application of nanotechnology in medicinal and biological fields has attracted a great interest in the recent yeras. In this paper the cell membrane leakage induced by iron nanoparticles (Fe-NP) against PC12 cell line which is known as a model of nervous system cell line was investigated by the lactate dehydrogenase (LDH) test. Therefore, PC12 cells were incubated with different concentration of Fe-NP and test was performed after 48h of incubation of the cells with Fe-NP. The resulting data showed that the Fe-NP induced the damage of PC12 cell membrane in a concentration dependent manner. Hence, it may be concluded that the different cytotoxicty effect of NPs may be referred to the concentration of NPs, type of the NPs and the cells. Indeed, the kind of cytotoxic impacts of NPs on the cells can be reduced by the considering of above-mentioned parameters. The resulting data showed that the Fe-NP induced the damage of PC12 cell membrane in a concentration dependent manner. Hence, it may be concluded that the different cytotoxicty effect of NPs may be referred to the concentration of NPs, type of the NPs and the cells. Indeed, the kind of cytotoxic impacts of NPs on the cells can be reduced by the considering of above-mentioned parameters.